Discovery of Nuclear DNA-like RNA (dRNA, hnRNA) and Ribonucleoproteins Particles Containing hnRNA - Georgiev, G.P. (Acta Naturae, 2016)
On August 9–11, 2014, Cold Spring Harbor (USA) hosted a special symposium dedicated to the discovery of messenger or informational RNA and the main events in the subsequent studies of its synthesis, regulation of synthesis, maturation, and transport. The existence of mRNA in bacteria was first suggested in 1961 by Jacob and Monod, based on genetic studies [1]. The same year, Brenner et al. confirmed the hypothesis [2]. Our laboratory played a key role in the discovery of messenger RNA in eukaryotes, as well as in the discovery of the nuclear ribonucleoproteins that contain it and in the elucidation of their structural organization. Therefore, I was invited to represent Russia at the Symposium and deliver a speech on these topics. However, my visa had only been issued after the end of the Symposium, and, therefore, the presentation was delivered by my former colleague G.N. Yenikolopov, who works at Cold Spring Harbor Laboratory. The transcript of the lecture is presented below.